Microscopy Characterization of Silica-Rich Agrowastes to be used in Cement Binders: Bamboo and Sugarcane Leaves. (7th September 2015) - Roselló, Josefa; Soriano, Lourdes; Santamarina, M. Pilar; Akasaki, Jorge L.; Melges, José Luiz P.; Payá, Jordi
Abstract: Agrowastes are produced worldwide in huge quantities and they contain interesting elements for producing inorganic cementing binders, especially silicon. Conversion of agrowastes into ash is an interesting way of yielding raw material used in the manufacture of low-CO2 binders. Silica-rich ashes are preferred for preparing inorganic binders. Sugarcane leaves ( Saccharum officinarum, SL) and bamboo leaves ( Bambusa vulgaris, BvL and Bambusa gigantea, BgL), and their corresponding ashes (SLA, BvLA, and BgLA), were chosen as case studies. These samples were analyzed by means of optical microscopy, Cryo-scanning electron microscopy (SEM), SEM, and field emission scanning electron microscopy. Spodograms were obtained for BvLA and BgLA, which have high proportions of silicon, but no spodogram was obtained for SLA because of the low silicon content. Different types of phytoliths (specific cells, reservoirs of silica in plants) in the studied leaves were observed. These phytoliths maintained their form after calcination at temperatures in the 350–850°C range. Owing to the chemical composition of these ashes, they are of interest for use in cements and concrete because of their possible pozzolanic reactivity. However, the presence of significant amounts of K and Cl in the prepared ashes implies a limitation of their applications.